2023
DOI: 10.3390/machines11040480
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Tool Wear Detection in CNC Machines Based on Fusion Flux Current of Motor and Image Workpieces

Abstract: In the manufacturing industry, computer numerical control (CNC) machine tools are of great importance since the processes in which they are used allow the creation of elements used in multiple sectors. Likewise, the condition of the cutting tools used is paramount due to the effect they have on the process and the quality of the supplies produced. For decades, methodologies have been developed that employ various signals and sensors for wear detection, prediction and monitoring; however, this field is constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Online assessments of tool wear are usually conducted by inferring the tool wear from the monitoring signals [4]. Commonly used monitoring signals are cutting force [5,6], vibration [7], acoustic emission [8], and rotor current [9]. Because of its ability to sense tool wear condition, the cutting force signal has been widely adopted in tool wear monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Online assessments of tool wear are usually conducted by inferring the tool wear from the monitoring signals [4]. Commonly used monitoring signals are cutting force [5,6], vibration [7], acoustic emission [8], and rotor current [9]. Because of its ability to sense tool wear condition, the cutting force signal has been widely adopted in tool wear monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey conducted across multiple manufacturing facilities, it was found that manual tool wear observation accounts for approximately 30% of unscheduled machine downtime due to incorrect assessments and the time needed for inspections. Moreover, the subjectivity of these methods introduces variability in tool wear assessment across different operators, making it challenging to establish consistent maintenance schedules [2,3].…”
Section: Introductionmentioning
confidence: 99%